2021
DOI: 10.7759/cureus.18084
|View full text |Cite
|
Sign up to set email alerts
|

Suicide by Opioid: Exploring the Intentionality of the Act

Abstract: Opioid toxicity can result in life-threatening respiratory depression. Opioid-overdose mortality in the United States is high and increasing, but it is difficult to determine what proportion of those deaths might actually be suicides. The exact number of Americans who died of an opioid overdose but whose deaths might be classified as suicide remains unknown. It is important to differentiate between those who take opioids with the deliberate and unequivocal objective of committing suicide, that is, those with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Data from more recent months may represent an undercount in suicides, although we cross-checked current and previous counts for the four months from 1st April 2020 for countries/areas-within countries that were in our earlier study 4 and found an average increase of <5%. Suicides may not have been as well captured as usual during the pandemic because of parallel events and/or resourcing issues (e.g., there are concerns that some US suicides are now being recorded as drug overdoses because they are occurring alongside the opioid crisis and medical examiners and coroners have been overwhelmed with COVID-19 deaths 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from more recent months may represent an undercount in suicides, although we cross-checked current and previous counts for the four months from 1st April 2020 for countries/areas-within countries that were in our earlier study 4 and found an average increase of <5%. Suicides may not have been as well captured as usual during the pandemic because of parallel events and/or resourcing issues (e.g., there are concerns that some US suicides are now being recorded as drug overdoses because they are occurring alongside the opioid crisis and medical examiners and coroners have been overwhelmed with COVID-19 deaths 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…36 However, discerning unintentional from intentional misuse/ abuse and suicide attempts may be difficult as the intentionality of overdose tends to be dimensional rather than categorical with shared risk factors. 36,37 Multivariable analyses showed that all co-used medications except antidepressants and NSAIDs were associated with significantly increased risks of noncritical and critical care admissions, and each additional medication increased such risks substantially. These findings largely support our hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…36 However, discerning unintentional from intentional misuse/abuse and suicide attempts may be difficult as the intentionality of overdose tends to be dimensional rather than categorical with shared risk factors. 36,37…”
Section: Discussionmentioning
confidence: 99%
“…According to estimates by the Centres for Disease Control and Prevention (CDC), suicides account for approximately 7% of all opioid overdose deaths. Opioids may lead to the occurrence of opioid use disorder (OUD) and thus cause abnormalities in the course of mental processes, including the reward system [21]. Q.…”
Section: Introductionmentioning
confidence: 99%